(untitled) (Delito y Sociedad, 2019)
The purpose of this article is to contribute to understand, from a sociological perspective, the internal and external dynamics of criminal justice in Argentina. In this sense, we shall seek to track the specificities of the work performed by the latter and how other players affect the configuration of such specificities, if that were the case. For that purpose, we shall begin by mentioning the current disciplines and activities that take criminal justice as an object of exploration different from others. Then we shall move on to develop concepts from which we can analyze the operation of institutions and agencies involved in the criminal phenomenon. After that, we shall point out the importance of some ground-breaking investigations as models for the consolidation of a genuine sociology of criminal justice in our country. Finally, we shall raise a few questions that may enable us to locate criminal courts in a different analytical place, as these courts need to be explored as one of the factors, and not the least important factor, that contribute to «translate» certain social causes into specific criminal effects.